Structural dynamics - Williams, Martin (CRC Press, Taylor & Francis Group, 2016)
This book begins by describing dynamic systems and their representation for analytical purposes, then linear analysis of single- (SDOF) and multi-degree-of-freedom (MDOF) systems, under free vibration and in response to a variety of forcing functions. Hand analysis of continuous systems, methods of calculation of non-linear dynamic response, and the key principles of random vibration analysis are discussed.